Atypical presentation of pediatric BRAF RASopathy with acute encephalopathy. Issue 12 (21st November 2018) - Pezzani, Lidia; Marchetti, Daniela; Cereda, Anna; Caffi, Lorella G.; Manara, Ornella; Mamoli, Daniela; Pezzoli, Laura; Lincesso, Anna R.; Perego, Loredana; Pellicioli, Isabella; Bonanomi, Ezio; Salvoni, Laura; et al.
Abstract : We report a 9‐year‐old girl with hypotonia, severe motor delay, absent speech, and facial dysmorphism who developed acute encephalopathy with severe neurological outcome. Trio‐based whole exome sequencing (WES) analysis detected a de novo heterozygous mutation in the BRAF gene leading to the diagnosis of an atypical presentation of cardiofaciocutaneous (CFC) syndrome. This is the second case of CFC syndrome complicated with acute encephalopathy reported in the literature and supports the hypothesis that acute encephalopathy might be one of the complications of the syndrome due to an intrinsic susceptibility to this acute event. The report furthermore highlights the role of WES in providing a fast diagnosis in patients in critical conditions with atypical presentation of rare genetic syndromes.